The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/978-3-031-04083-2_14
|View full text |Cite
|
Sign up to set email alerts
|

ECQ$$^{\text {x}}$$: Explainability-Driven Quantization for Low-Bit and Sparse DNNs

Abstract: The remarkable success of deep neural networks (DNNs) in various applications is accompanied by a significant increase in network parameters and arithmetic operations. Such increases in memory and computational demands make deep learning prohibitive for resource-constrained hardware platforms such as mobile devices. Recent efforts aim to reduce these overheads, while preserving model performance as much as possible, and include parameter reduction techniques, parameter quantization, and lossless compression te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…We find, however, that (maximizing) the activation of a latent encoding by a given data point does not always correspond to its utility to the model in an inference context (see, for example, ref. 44 or Supplementary Fig. 7), putting the faithfulness of activation-based example selection for latent concept representation into question.…”
Section: Relmax In Briefmentioning
confidence: 99%
“…We find, however, that (maximizing) the activation of a latent encoding by a given data point does not always correspond to its utility to the model in an inference context (see, for example, ref. 44 or Supplementary Fig. 7), putting the faithfulness of activation-based example selection for latent concept representation into question.…”
Section: Relmax In Briefmentioning
confidence: 99%
“…On the other hand, the AI algorithms that now often perform best (for example, Deep Learning) are the least explainable, causing a demand for explainable models that can achieve high performance. Some researchers have exploited this area, including authors of [269] significantly reduce the trade-off between efficiency and performance by introducing XAI for DNN into existing quantization techniques. And authors of [270] demonstrated that the wavelet modifications provided could lead to significantly smaller, simplified, more computationally efficient, and more naturally interpretable models, while simultaneously keeping performance.…”
Section: ) Trade-off Between Performance and Explainabilitymentioning
confidence: 99%